Multiple Injections Study Based on an Advanced Combustion Investigation System. (August 2015) - Yu, Wenbin; Yang, Wenming; Mohan, Balaji; Tay, Kunlin; Zhao, Feiyang; Chou, Siaw Kiang
Abstract: An advanced combustion investigation system was established in this paper. Based on this system, the multiple-injection spray development under various operating conditions was presented. The experiment result shows that the effect of ambient pressure and injection pressure on multiple injection spray are very conspicuous, especially the effect of injection fluctuation on multiple injections.